COMPUTATIONAL MODELING OF A REGULAR WAVE TANK - Gomes, M. N.; Olinto, C. R.; Rocha, L. A. O.; Souza, J. A.; Isoldi, L. A. (Revista de Engenharia Térmica, 2009)
This paper presents two different numerical methodologies to generate regular gravity waves in a wave tank. We performed numerical simulations of wave generation through the FLUENT® package, using the Volume of Fluid (VOF) multiphase model to reproduce the wave propagation in the tank. Thus it was possible to analyze two methods for generating regular waves that could be used in future work, especially in the study of devices of energy conversion from ocean waves into electrical energy.